EVALUATION FOR IMPACT OF CLIMATE CHANGE ON WHEAT (TRITICUM AESTIVUM L.) GRAIN QUALITY AND YIELD TRAITS - SHAMIM, S; ABDULLAH, M; SHAIR, H; AHMAD, J; FAROOQ, MO; AJMAL, S (Biological and Clinical Sciences Research Journal, 2024)
Climate change is increasing stress on agricultural production, notably in developing nations where crop yields are critically impacted. Swift changes in climate conditions directly diminish wheat yields and adversely influence key grain constituents such as starch, fibre, protein, amino acids, and essential nutrients. The studies were conducted for six years, from 2017-18 to 2022-23, to understand the impact of changing climate on wheat grain composition and quality. The results indicated that November is the best month for sowing wheat. The post-anthesis drought or less water availability helps the plants accumulate more protein and gluten contents, and starch contents decrease. The quality of the grain, however, is more significantly influenced by the variety of wheat, the type of environmental stress, and the duration and severity of exposure. Faisalabad 08 had the highest protein and gluten contents, while Galaxy 13 had the highest starch contents in D2. Galaxy 13 indicated the highest value of test weight and 1000-grain weight in November.